PENYERAPAN ION LOGAM Pb(II) DARI LARUTAN MENGGUNAKAN SERBUK DAUN PURING (Codiaeum variegatum) - Fitriani, Fitriani (Jurnal Pendidikan Matematika dan IPA, 2017)
The adsorption of metal ion Pb(II) by croton leaf powder through the activation of hydrochloric acid (HCl) or chemical methods has been researched. The research aimed to determine the optimum condition of croton leaf powder as adsorbent by variation of contacting time (30, 60, 90 and 120 minutes) and the difference in mass of adsorbent (1; 2; 3 and 4 grams ). This research began with downsizing the size of croton leafs become to 100 mesh, then was performed chemical activation by soaking the croton leaf powder with 2 N HCl. The adsorption was conducted by contacting the adsorbent with a solution of the sample based on contacting time and mass of adsorbent, then analyzed by Atomic Absorption Spectrophotometer (AAS). The result showed that the optimum condition of adsorption was achieved at 4 grams adsorbent by contacting time in the 60 minutes with Pb(II) adsorbed 1,76 mg/L or 35,2 %. Based on this findings, we concluded that the increase in mass of adsorbent increased the adsorption power of metal ion Pb(II) by optimum contacting time. Keywords: adsorption, croton leaf powder, metal ion Pb(II)